An induced population of Trypanosoma cruzi epimastigotes more resistant to complement lysis promotes a phenotype with greater differentiation, invasiveness, and release of extracellular vesicles - Rossi, Izadora Volpato; Nunes, Maria Alice Ferreira; Sabatke, Bruna; Ribas, Hennrique Taborda; Winnischofer, Sheila Maria Brochado; Ramos, Augusto Savio Peixoto; Inal, Jameel Malhador; Ramirez, Marcel Ivan (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease is a neglected tropical disease caused by Trypanosoma cruzi, which uses blood-feeding triatomine bugs as a vector to finally infect mammalian hosts. Upon entering the host, the parasite needs to effectively evade the attack of the complement system and quickly invade cells to guarantee an infection. In order to accomplish this, T. cruzi expresses different molecules on its surface and releases extracellular vesicles (EVs). Here, we have selected a population of epimastigotes (a replicative form) from T. cruzi through two rounds of exposure to normal human serum (NHS), to reach 30% survival (2R population). This selected population had a favored metacyclogenesis compared to wild-type (WT) parasites. 2R metacyclic trypomastigotes had a two-fold increase in resistance to complement mediated-lysis and were at least three times more infective to eukaryotic cells, probably due to a higher Gp82 expression in the resistant population. Moreover, we have shown that EVs from resistant parasites can transfer the invasive phenotype to the WT population. In addition, we showed that the virulence phenotype of the selected population remains in the trypomastigote form derived from cell culture, which is more infective and also has a higher rate of release of trypomastigotes from infected cells. Altogether, this data indicates that it is possible to select parasites after exposure to a particular stress facdtor and that the phenotype of epimastigotes remained in the infective stage. Importantly, EVs seem to be an important virulence-increasing mechanism in this context of survival and persistence in the host.